Growth and Adjustment in IMF-Supported Programs. (Independent Evaluation Office Reports, 2021)
This evaluation assesses how well IMF-supported programs helped to sustain economic growth while delivering adjustment needed for external viability over the period 2008-19. The evaluation finds that the Fund's increasing attention to growth in the programs has delivered some positive results. Specifically, it does not find evidence of a consistent bias towards excessive austerity in IMF-supported programs. Indeed, programs have yielded growth benefits relative to a counterfactual of no Fund engagement and boosted post-program growth performance. Notwithstanding these positive findings, program growth outcomes consistently fell short of program projections. Such shortfalls imply less protection of incomes than intended, fuel adjustment fatigue and public opposition to reforms, and jeopardize progress towards external viability. The evaluation examines how different policy instruments were applied to support better growth outcomes while achieving needed adjustment. Fiscal policies typically incorporated growth-friendly measures but with mixed success. Despite some success in promoting reforms and growth, structural conditionalities were of relatively low depth and their potential growth benefits were not fully realized. Use of the exchange rate as a policy tool to support growth and external adjustment during programs was quite limited. Lastly, market debt operations were useful in some cases to restore debt sustainability and renew market access, yet sometimes were too little and too late to deliver the intended benefits. The evaluation concludes that the IMF should seek to further enhance program countries' capacity to sustain activity while undertaking needed adjustment during the program and to enhance growth prospects beyond the program. Following this conclusion, the report sets out three recommendations aimed at strengthening attention to growth implications of IMF-supported programs, including the social and distributional consequences.